PERANAN KOMPUTER SEBAGAI MEDIA PEMBELAJARAN BAGI ANAK - Pujiriyanto Pujiriyanto (Dinamika Pendidikan, 2009)
There is a missconception that computer would make the children being isolate. but in fact computer is usefull to teach social skill to the children. Physically a classroom without access to computer as a potential learning resources result in all isolation environment. Consequently it is very important for  the children familiar  with computer earlier as an instructional media. Children should be taught  about  computer  advantage  in  order  to  improve  children  learning capability and self confident. There is no doubt where the children interest to computer games and television programs.  This condition should be catched sight of as learning modality. By providing educate computer programs to the children will emerge a powerful! As learning media. Children not only become skilled at computer technical skill but understanding the use of computer WI a learning tool. contrasting to entenainment tool. The finest way to dig up most favorable  optimum  computer  advantage  it is strongly  need fo parent  and teacher is proficient  with best educate computer program.  Teacher must be competence to integrate use of computer as learning and focus  in high order thingking skill.Keyword: Computer. children. media